E-Business Designing Interface "Petani Sejahtera" Based on Mobile Application - Gilang Pratama Putra; Ari Purno Wahyu Wibowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The monitoring information system is an android application that is made to make it easier to distribute crop yields so that no accumulation results in wasted crops, especially this "Petani Sejahtera" application is made for the welfare of farmers by distributing their harvests to those who are willing to accommodate the harvest. Farmers in the field provide actual data based on the initial planting to harvesting. With the creation of a User Interface (UI) design on an Android-based mobile application, it is intended that managers can directly connect and interact with products from farmers, which later managers can help distribute crops. This User Interface (UI) design aims to sell farmers' yields by making various features in the "Petani Sejahtera" application. It aims to make it easier for farmers from the beginning of the planting process to the harvesting process so that later the data can be used as a comparison for both the manager and the farmers themselves. With the application of "Petani Sejahtera", it is hoped that there will no longer be an accumulation of harvests, distribution channels of sales will become even, and farmers will have other options so as not to sell their crops to irresponsible persons by monopolizing the market prices. Application to design the display interface uses Figma. Figma is an application to create an overview of the user interface before it is applied to manufacture android-based applications.